Current insights into the effects of cationic biocides exposure on Enterococcus spp. - Pereira, Ana P.; Antunes, Patrícia; Peixe, Luísa; Freitas, Ana R.; Novais, Carla (Frontiers in Microbiology, 2024)
Cationic biocides (CBs), such as quaternary ammonium compounds and biguanides, are critical for controlling the spread of bacterial pathogens like Enterococcus spp., a leading cause of multidrugresistant healthcare-associated infections. The widespread use of CBs in recent decades has prompted concerns about the potential emergence of Enterococcus spp. populations exhibiting resistance to both biocides and antibiotics. Such concerns arise from their frequent exposure to subinhibitory concentrations of CBs in clinical, food chain and diverse environmental settings. This comprehensive narrative review aimed to explore the complexity of the Enterococcus' response to CBs and of their possible evolution towards resistance. To that end, CBs' activity against diverse Enterococcus spp. collections, the prevalence and roles of genes associated with decreased susceptibility to CBs, and the potential for co-and cross-resistance between CBs and antibiotics are reviewed. Significant methodological and knowledge gaps are identified, highlighting areas that future studies should address to enhance our comprehension of the impact of exposure to CBs on Enterococcus spp. populations' epidemiology. This knowledge is essential for developing effective One Health strategies that ensure the continued efficacy of these critical agents in safeguarding Public Health.